Muscle Strength, Oxygen Saturation and Physical Activity in Patients with Chronic Exertional Compartment Syndrome Compared to Asymptomatic Controls - Lisa Urup Tønning; Bjarne Mygind-Klavsen; Troels Kjeldsen; Ulrik Dalgas; John Brincks; Inger Mechlenburg (International Journal of Sports Physical Therapy)
# Background